An assessment of the microbiological water quality of sand dams in southeastern Kenya - Quinn, Ruth; Avis, Orlando; Decker, Manon; Parker, Alison; Cairncross, Sandy (MDPI, 2018)
Sand-storage dams have proven to be a successful water harvesting method and potential solution to water and food security issues in semi-arid regions such as south east Kenya. This paper examines the microbiological quality of water both contained in the sand dam via test holes and abstracted from it through covered wells and scoop holes. In total, the values of thermotolerant coliform (TTC) concentration, turbidity, and pH are presented for 47 covered wells, 36 scoop holes, and 29 test holes, as well as the conductivity values in conductivity in 39 covered wells and 11 scoop holes. The water from test holes and covered wells was microbiologically of better quality than the scoop holes with median TTC levels of 0/100 mL and 159/100 mL respectively. However, the median values of turbidity for both scoop holes (20–30 NTU) and covered wells (5–10 NTU) exceed the World Health Organisation (WHO) guideline values. In addition the conductivity of water from 23% of scoop holes and 26% of covered wells is above the recommended WHO limit. This study also found that sanitary surveys are not a useful indicator of water quality in sand dams; however, they can identify areas in which sanitation and improvement of water sources are needed.
Keywords: Microbiology; Faecal contamination; Sand dam; Sanitary inspection